2016
DOI: 10.1002/pon.4298
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation modeling of the relationship between posttraumatic growth and psychosocial factors in women with breast cancer

Abstract: This study indicated the role of coping strategies and social support in enhancing PTG in Japanese women with BC. Furthermore, perceived social support, a positive approach coping style, and PTG may reduce depressive symptoms. Our results suggest that health care professionals should consider whether patients receive enough support from others, and whether the patients are using the appropriate coping style to adapt to stressors associated with the diagnosis and treatment of BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
(120 reference statements)
4
29
1
1
Order By: Relevance
“…Cordova, Cunningham, Carlson and Andrykowski (11) began studying predictors in populations of women with breast cancer evaluating their well-being, social support, life threat perception, active verbalization about cancer and time after diagnosis. Later, other studies pursued the establishment of variables that were correlated to a greater PTG score and that explained this model (9,(12)(13)(14) . Different authors concluded that rumination, social support, the use of adaptive coping strategies and the perception of the experienced situation as actually stressing have proven to be major predictors of a greater PTG (11,14,15) .…”
Section: Introductionmentioning
confidence: 99%
“…Cordova, Cunningham, Carlson and Andrykowski (11) began studying predictors in populations of women with breast cancer evaluating their well-being, social support, life threat perception, active verbalization about cancer and time after diagnosis. Later, other studies pursued the establishment of variables that were correlated to a greater PTG score and that explained this model (9,(12)(13)(14) . Different authors concluded that rumination, social support, the use of adaptive coping strategies and the perception of the experienced situation as actually stressing have proven to be major predictors of a greater PTG (11,14,15) .…”
Section: Introductionmentioning
confidence: 99%
“…A recent term for the positive psychological changes individuals experience following stressful events, coined by Tedeschi and Calhoun, is posttraumatic growth (PTG). Posttraumatic growth is defined as “the experience of positive change that occurs as a result of the struggle with highly challenging life crises.” Evidence suggests that PTG is relatively common among women with breast cancer and exhibits an increasing tendency among early‐stage breast cancer survivors over a 6‐month period . Posttraumatic growth has many related factors, such as age, education, economic status, treatment, social support, and support from significant others …”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was still positively correlated with optimism (24) . Women who reported having a religion had higher scores than those who did not report (25,28) . Samples that reported worse health presented lower PTG scores compared to women with fewer side effects (26) .…”
Section: Posttraumatic Growthmentioning
confidence: 83%
“…On the study of Kroemeke et al (29) , social support showed no correlation with PTG, and was therefore not included on the model tested for predictor analysis. On the other hand, on the study of Tomita et al (28) the variable only affected the factor relating to others, being important especially when coming from one's spouse.…”
Section: Social Supportmentioning
confidence: 94%
See 1 more Smart Citation